PENGARUH FAKTOR GEOGRAFIS DAN DEMOGRAFIS DALAM KEPUTUSAN PEMBELIAN (STUDI KASUS PADA KONSUMEN UMKM DI KAWASAN WISATA PANTAI KOTA BENGKULU) - Tedy Sunardi; Fikri, Muhammad (Universitas Muhammadiyah Bengkulu, 2024)
This research aims to determine the influence of geographic and demographic factors in purchasing decisions (case study of MSME consumers in the coastal tourism area of ​​Bengkulu City). This research uses a quantitative approach with research methods based on the philosophy of positivism. The population used in this research was MSME consumers in the Long Beach tourist area of ​​Bengkulu City. Respondents were selected using a purposive sampling technique with a sample size of 130 people. Data was collected through a validated and reliable questionnaire. The data analysis technique used is multiple regression to test the hypothesis. The test results show that geographical factors (t_count = 3.018, Sig = 0.003) and demographic factors (t_count = 5.688, Sig = 0.000) have a positive and significant effect on individual purchasing decisions. Simultaneously, these two factors together have a significant influence on purchasing decisions (F_count = 28.354, Sig = 0.000).